Frederick Weyerhaeuser and the American West - Healey, Judith Koll (Book collections on Project MUSE., 2013)
A new biography of Frederick Weyerhaeuser (1834-1914), one of the great industrialists of the late nineteenth and early twentieth centuries and founder of the international timber corporation the Weyerhaeuser Company. Author Judith Koll Healey narrates the life of this extraordinary man through newly available resources: his extensive correspondence and journal entries as well as the letters and diaries of family members, friends, and business associates from around the country. She frames Weyerhaeuser's many commercial opportunities and business decisions within both the family's internal dynamics and world events: war and unrest, economic upswings and downturns, and western expansion and eastern urbanization. Throughout, Healey offers a thoughtful perspective on his achievements as well as the limitations of his vision for the expansion of the American West. --